A recent update on fucoidonase: source, Isolation methods and its enzymatic activity - Barzkar, Noora; Rungsardthong, Vilai; Tamadoni Jahromi, Saeid; Laraib, Qandeel; Das, Rakesh; Babich, Olga; Sukhikh, Stanislav (Frontiers in Marine Science, 2023)
Brown seaweeds are a source of bioactive polysaccharides and the most studied seaweeds for fucoidanases. Fucoidanases are hydrolytic enzymes that can hydrolyze the complex polymer fucoidan to low molecular weight fucoidan without removing its side substituent groups. To date, no established quantitative methods for determining the activity of fucoidanases are available. Hence, this review article has been organized in such a manner to get an overview of existing sources, techniques to isolate, downstream, and potential applications of fucoidanases. It has been well established that brown algae can synthesize linear as well as extensively branched polysaccharides containing a species-specific sugar moiety in the arrangement of fucoidan, which contributes to the exceptional diversity of its structural forms. An intracellular fucoidanase isolated from seaweed was found to hydrolyze 1, 3-α-glycosidic bonds and also possess deacetylase activity against acetylated fucoidans. Moreover, the fucoidanases are isolated from marine bacteria, algae, fungi, mollusks, echinoderms, etc. Apart from its sources, isolation, concentration methods, and the type of chromatographic columns available yet, further aspects i.e. total protein, total activity, degree of purification, and specific activity of marine fucoidan have also been highlighted in this review article. Besides, the effect of inhibitors and activators on fucoidanase activity has also been reviewed to create a better understanding. It is proclaimed that the hydrolytic action of fucoidanase on fucoidan yields several octal- and decasaccharides having unique properties and can be exploited for bioactive oligosaccharides possessing antioxidant, anti-inflammatory, antiangiogenic, anticancer, antiviral, prebiotic and anticoagulant effects additionally, boost blood profile and also strengthen cognitive skills in the human body.